Kesiapsiagaan Masyarakat Terhadap Bencana di Objek Wisata Ujong Blang Lhokseumawe - Anismar Anismar; Muchlis Muchlis; Ainol Mardhiah; Ade Muana Husniati; Miswar Miswar (Jurnal Solusi Masyarakat (JSM), 2026)
The Ujong Blang Beach tourism area in Lhokseumawe City is highly vulnerable to various coastal hazards, including coastal erosion, tidal flooding, storm surges, extreme weather, and potential tsunamis. However, the preparedness capacity of the local community, tourism stakeholders, and visitors has not adequately kept pace with these risks. The low level of disaster literacy, the absence of standard operating procedures (SOPs) for emergency response, limited evacuation routes, inadequate disaster mitigation information, and the suboptimal implementation of a community-based Early Warning System (EWS) constitute the primary challenges that require integrated intervention. This community service program aims to enhance the disaster preparedness capacity of the tourism community through the Community-Based Disaster Risk Reduction (CBDRR) approach, which positions local communities as the primary actors in disaster risk reduction efforts. The program is implemented through disaster education, mitigation training, evacuation drills, the development of evacuation routes, the establishment of community disaster response volunteers, and the strengthening of a simple community-based early warning system tailored to local social conditions. A participatory approach is adopted by involving village authorities, Tourism Awareness Groups (Pokdarwis), micro, small, and medium enterprises (MSMEs), community leaders, and other relevant stakeholders to establish sustainable coordination and preparedness mechanisms. The expected outcomes include improved knowledge, skills, and awareness of disaster preparedness among community members, the availability of disaster mitigation facilities and evacuation routes, the establishment of an effective risk communication mechanism, and increased visitor awareness of safety measures. The implementation of CBDRR and a community-based EWS is expected to transform Ujong Blang into a safe, resilient, adaptive, and sustainable coastal tourism destination while strengthening collaboration among higher education institutions, government agencies, and local communities in supporting disaster risk reduction.